Implementation of Authentic Assessment in Learning the Indonesian Language - Rahmawati Rahmawati (Universitas Negeri Makassar, 2021)
Abstract. This study aims to describe the implementation of authentic assessment in learning the Indonesian Language at Senior High School 1 Wonomulyo. The description of the implementation of the authentic assessment includes a description of the authentic assessment model carried out by the Indonesian language teacher. The type of research used is qualitative research with a descriptive qualitative research design. The population and sample in this study were two Indonesian language teachers at Senior Hight School 1 Wonomulyo. The data in this study were obtained through interviews, observations, and document analysis. The data were analyzed using qualitative data analysis techniques through four stages, namely: data collection, data reduction, data presentation, and concluding. The validity of the research data was obtained through the process of data triangulation. The results of the study indicate that the teacher has carried out an authentic assessment in learning the Indonesian Language under the provisions of the curriculum applied by the school. However, the implementation of the assessment is not following what is stated in the lesson plan. The assessment is adjusted to the conditions of the class and the material being taught. In the assessment of attitude competence, the teacher uses observations during the learning process and in various models of learning activities. In the assessment of knowledge competence, the teacher uses a written assessment. Meanwhile, in the assessment of skills competence, the teacher uses performance assessment, peer assessment, and open interviewsKeywords: Implementation of authentic assessment, authentic assessment model, learning Indonesian language